2022
DOI: 10.1021/acs.jpcc.2c04862
|View full text |Cite
|
Sign up to set email alerts
|

Silicate Phosphors BaGa2Si2O8:Ln3+ (Er3+, Ho3+, Yb3+) Equipped with Intrinsic Optical Bistability toward Photonic Barcodes

Abstract: Optical bistability phenomenon is of vital significance for technological applications such as optical telecommunications. Herein, novel upconversion (UC) luminescence phosphors, Ln 3+ (Er 3+ , Ho 3+ )/Yb 3+ co-doped BaGa 2 Si 2 O 8 , were developed. Irradiated by 980 nm laser, the system showed intrinsic optical bistability (IOB) and two different optical responses were observed under the same incident pump power, signifying that these phosphors can play a role in optical switching devices. This nonlinear phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Obviously, the increase of incident pump power does not result in the presence of any new emission band but enhances the existing emissions. As a nonlinear behavior, the relationship between UC emission intensity and laser excitation power can be described using the following formula: where I up signifies the integrated luminescence intensity, P refers to the incident pump power, and n is the number of incident photons involved in the transition process of lanthanide ions from the ground state to the emitting excited state. The values of n can be deduced via calculating the slope of the double logarithmic plot of luminescence intensity versus the incident pump power, as shown in Figure b and d. The n values can be determined to be ∼1.88, 1.94, 2.37, 2.06, and 1.63, so it is concluded that the two-photon process is largely responsible for all the UC emissions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, the increase of incident pump power does not result in the presence of any new emission band but enhances the existing emissions. As a nonlinear behavior, the relationship between UC emission intensity and laser excitation power can be described using the following formula: where I up signifies the integrated luminescence intensity, P refers to the incident pump power, and n is the number of incident photons involved in the transition process of lanthanide ions from the ground state to the emitting excited state. The values of n can be deduced via calculating the slope of the double logarithmic plot of luminescence intensity versus the incident pump power, as shown in Figure b and d. The n values can be determined to be ∼1.88, 1.94, 2.37, 2.06, and 1.63, so it is concluded that the two-photon process is largely responsible for all the UC emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the spectral purity is evaluated through calculating the integrated intensities of green and red emission bands to check the quality of the luminescence color in the materials. The spectral purity can be estimated according to eq : where I g and I r are the integrated intensities of green emission and red emission bands, respectively. It is indisputable that the S gr value is limited in the interval from −1 and +1, and the former means a pure red emission, while the latter represents a pure green emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, one of the most important applications of lanthanides in their ionized form is realized in modern lighting technologies as active dopants in inorganic and/or organic matrices. Regarding inorganic phosphors, optically active ions are usually incorporated into the crystal lattice of different compounds, such as aluminates, 2,3 borates, 4,5 silicates, 6–8 and phosphates. 9–11 Among them, titanates, particularly Ruddlesden–Popper (RP) compounds, described by the chemical formula A n +1 B n O 3 n +1 attract more attention due to their layered perovskite type of structure that allows their use in photocatalysis, solar cells, optoelectronics, and solid-state lighting.…”
Section: Introductionmentioning
confidence: 99%
“…At present, counterfeiting and information leakage seriously threaten people’s interests to physical and mental health. Consequently, there is an urgent demand for new anti-counterfeiting technologies for minimizing economic damage and protecting public safety. Compared to the traditional technologies, such as QR codes, bar code, hologram, watermarking, engraving gravure printing technology, and digital security technology, the luminescence anti-counterfeiting technique has been widely adopted due to its facile design, excellent concealment, and high stability. However, most of the traditional fluorescent materials used for anti-counterfeiting have shortcomings such as monochrome emission and fixed excitation, which reduce the anti-counterfeiting level and can be easily forged. Therefore, it cannot satisfy the actual needs of people. Thus, there is an urgent need to develop innovative multiple anti-counterfeiting luminescent materials with intentionally designed color or well-defined tunable properties for information security. , …”
Section: Introductionmentioning
confidence: 99%